2019
DOI: 10.3390/f10111002
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Stock Type and Forest Vegetation Management Treatments on Douglas-Fir Seedling Growth and Survival—Ten-Year Results

Abstract: In the Pacific Northwest, the use of forest vegetation management (FVM) and seedling stock type selection are important tools to ensure seedling establishment according to organizational objectives and state laws. Individually, these two reforestation decisions have been shown to increase growth and survival of Douglas-fir seedlings, however, the interaction between seedling stock type and level of vegetation control represents economic and ecologic tradeoffs that are less well understood. This study was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…The positive effect of individual attributes related to seedling vigour, represented in this study by the values of height at planting, was confirmed in both contexts (Tables 3, 5 and 6 and Figure 3) [36]. However, initial height contributes very little to explaining the variation in annual apical growth.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The positive effect of individual attributes related to seedling vigour, represented in this study by the values of height at planting, was confirmed in both contexts (Tables 3, 5 and 6 and Figure 3) [36]. However, initial height contributes very little to explaining the variation in annual apical growth.…”
Section: Discussionsupporting
confidence: 71%
“…In the flysch_mixed site group, in which fir was subdominant prior to fire, growth rate was positively affected in the first year after planting compared to ls_fir and negatively thereafter ( Table 5 and Figure 3). Probably resprouting evergreen and deciduous broadleaf plants had a nurse effect in the first year, which fades later on [39] (see also [36]) and/or the very low clay content of the soils in these sites drastically reduced water stress during the early phase of establishment compared to the other sites, from then on the unsuitability of the sites compared to the others surfaced [20]. The negative effect is stronger in higher quantiles indicating a genuine limiting factor from year 2 of the study onward.…”
Section: Discussionmentioning
confidence: 99%
“…In the longer term, without additional brushing or thinning treatment it is expected that overall stand productivity of these brushed sites will partition into broadleaf and Douglas-fir components resulting in complex stand dynamics dependent on species productivity, competition intensity, density and canopy occupancy. Also, concerns over climate change and the increased frequency of seasonal drought in southern BC forests have renewed interest in the potential for brushing treatments to increase the availability of soil moisture through reduced evaporative demand and soil moisture stress resulting in significant increases in survival and growth of planted Douglas-fir (Wightman et al 2019). Douglas-fir may utilize carbon assimilated by birch and shared, possibly, through ectomycorrhizal networks (Simard et al 1997); other resources may be shared as well (e.g., Gorzelak et al 2015), potentially providing some resilience to stresses exacerbated under a changing climate.…”
Section: Brushing and Stand Productivitymentioning
confidence: 99%
“…Substrates have been the subject of several studies over time for coniferous and deciduous species [23][24][25][26][27][28][29][30]. The influence of the substrate on the growth of containerized black locust seedlings was addressed in several studies.…”
Section: Introductionmentioning
confidence: 99%